Cowboys and the Imperial Ecology of Beef. Issue 1 (March 2022) - Hiltner, Aaron
Abstract : Beef creates an emotional resonance that far outstrips its place within the market. In the 2000s, chicken may have dethroned beef as the most common meat on American plates, ending its reign since the 1940s, but most people do not seem to associate chicken breasts or poultry farmers with national identity the way Americans see ribeyes and cowboys as symbols of the nation's muscular, frontier past.